Paternidade e separação conjugal: a perspectiva do pai - Bottoli, Cristiane (2010)
This research had as an objective to understand how paternity constitute itself in the conjugal separation and children guard context, throughout the fatherly figure for understanding that separation historically represents to fathers a moment where they are separated of their children. The research has a qualitative character and seeked to know more about the theme and to do so it‟s been developed semi-structured interviews with seven fathers that were going through the separation process and that for such reason seeked counselling at two juridical practice places that attend the community, in Santa Maria city. After the interviews had been done, a Content Analysis of the same had been applied which made it possible to stablish the following categories: being a father; conjugality and parenthood; guard; loss and suffer; the arising of a new father. The results point out that the conjugal separation has constituted itself as a moment that modifies the paternity exercise, in which meaningful differences occur in before and after mainly in regards to proximity with children and issues involving a relationship with ex-wife. Aspects that point out to inherent conflicts to the end of Conjugality and the maintenance of Parenthood were also identified. Other aspect that had been shown was the expressed desire by the fathers to be present in different moments in the children daily life. In regards to children guard it‟s been noticed a movement of the interviewed fathers in the sense to enlarge their participation. The same way the recognition of the maternal figure was present as that whom is naturally assigned to occupy this place. It can also be mentioned that the interviewed fathers have been seeked to built and rebuilt paternity at all moments, which is characteristical in the contemporary paternity exercise that considers a participative and present father. It‟s understood that the comprehension of this family reality throughout the father‟s point of view allowed to enlarge a glimpse over the phenomenum and made it possible a large understanding of the family‟s relationships dynamics in a current context.